Shift of English Literature Learning from Classroom to Online: Preferences and Attitude of Bangladeshi Undergraduate Students - Islam, Md. Zohorul (Universitas Lancang Kuning, 2021)
This paper explores the English Literature classes that are taught online in Bangladeshi universities and the attitude of the students towards these classes. The new-normal after the Covid-19 outbreak forced the students to attend classes online and their experience about the English Literature classes are investigated in this research. The total number of participants for this study was ninety-seven. The research was conducted on the students of the Department of English in four private universities in Bangladesh. A survey questionnaire was prepared consisting of twenty questions to collect the data online. The data was analysed with quantitative method of research. Digital statistical software Microsoft Excel used for the data analysis. The research finding shows that the students find poetry and short story classes effective and engaging in online classes but showed unfavorable attitude towards novel and drama classes. The results also show that the students want more opportunity to share their opinion in the class and preferred visual aids in online classes. This study implies that while the instructors and the students are going through an unprecedented challenge of learning English Literature in online classrooms, the obstacles can be mitigated through increasing interactive classroom discussion and precise use of multimedia tools while teaching different genres of English Literature.